Brown Adipose Tissue: A New Target for Antiobesity Therapy - Anna Meiliana; Andi Wijaya (The Indonesian Biomedical Journal, 2010)
BACKGROUND: Human fat consist of white and brown adipose tissue (WAT and BAT). Though most fat is energy-storing WAT, the thermogenic capacity of even small amounts of BAT makes it an attractive therapeutic target for inducing weight loss through energy expenditure.CONTENT: Over the past year, several independent research teams used a combination of positron-emission tomography and computed tomography (PET/CT) imaging, immunohistochemistry and gene and protein expression assays to prove conclusively that adult humans have functional BAT. BAT is important for thermogenesis and energy balance in small mammals and its induction in mice promotes energy expenditure, reduces adiposity and protects mice from diet-induced obesity. The thermogenic capacity of BAT is impressive. In humans, it has been estimated that as little as 50g of BAT could utilize up to 20% of basal caloric needs if maximally stimulated.SUMMARY: The obesity pandemic requires new and novel treatments. The past few years have witnessed multiple studies conclusively showing that adult humans have functional BAT, a tissue that has a tremendous capacity for obesity-reducing thermogenesis. Novel therapies targeting BAT thermogenesis may be available in the near future as therapeutic options for obesity and diabetes. Thermogenic ingredients may be considered as functional agents that could help in preventing a positive energy balance and obesity.KEYWORDS: brown adipose tissue, thermogenesis, energy expenditure, antiobesity therapy